PELATIHAN PEMBUATAN KONTEN DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN PRODUK ROTI AFIKA SARI - Tsaltsa Putri Ramadhany; Denia Maulani (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2024)
The development of technology and communication is currently changing almost all aspects of life such as the way we interact, work, and do business. Digital technology provides opportunities for anyone who can utilize it well. Small and medium businesses can utilize digital technology as a promotional medium or commonly called digital marketing. However, businesses still do not understand and apply digital marketing to their business due to a lack of knowledge about it. This problem also occurs in one of the bread businesses in Bojong Nangka Village named Afika Sari, the business owner said that the lack of knowledge related to digital marketing is an obstacle to the implementation of digital marketing. Therefore, training activities on digital marketing content creation through social media, especially Instagram and TikTok to increase sales of Afika Sari's bread products. The implementation of this activity consists of several stages of methods used, including training, mentoring, and evaluation. The result of this activity is the understanding of the Afika Sari bread business owner about digital marketing and the implementation of digital marketing in the business by creating Instagram and TikTok accounts.